Domination of vertex-edges in bipolar fuzzy graphs. (2021) - Umamageswari, D.; Parimala, M.
Abstract: In this article, the dominant vertex edge set was established using strong edges in bipolar fuzzy graphs. The subset T in V is described as the dominant vertex edge set in bipolar fuzzy graph G V, E if each strong edge e ∈ E, ∃ a vertex a ∈ T ∋ e incident on a . Also, some bounds in bipolar fuzzy graphs were described and characterized by the dominance number for the vertex edge γ vebf ( G ) . In addition, the dominance number for the vertex edge has been addressed in operations on bipolar fuzzy graphs with appropriate examples.